Stream-bank protection in narrow channel bends using 'barbs': A laboratory study - Matsuura, Troy (University of Ottawa (Canada), 2004)
This thesis reports on phases 1 and 2 (Matsuura and Townsend, 2004a, 2004b, 2004c) of an ongoing laboratory study of a novel form of streambank protection structure. 'Barbs' are groin-like structures designed to protect the (usually unstable) outside-bank regions of channel bends by actively redirecting flow away from the outside-bank. These low-profile, rock-fill structures have trapezoidal-shaped cross-sections and point upstream into the direction of flow. Their overall length typically extends one-quarter way across the channel, and are comprised of 'key' and 'weir' sections. The former, which is set back into the channel bank material, slopes downwards at 1V:1.5H to meet the low-profile weir section that extends into the stream. The crest of the weir section, the 'key' end of which should not exceed the channel-forming flow level (typically taken as the 1.5-year flow event), should have a mild positive slope (<1 V:5H) towards the 'stream' end for proper operation, (USDA 1999). By disrupting near-bank velocity gradients, barbs promote sediment deposition along the eroding outside-bank region. Their presence also modifies the bend's 'helicoidal'-type flow pattern such that secondary currents, that would otherwise attack the outside-bank, are redirected towards the center of the channel. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.